2012
DOI: 10.1590/s1517-83822012000400047
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal tolerance (Cr, Ag and Hg) in bacteria isolated from sewage

Abstract: Samples of sewage from a university hospital and a chemistry technical school were analysed for the percentage of bacterial tolerance to chromium (Cr), silver (Ag) and mercury (Hg). Additionally, we investigated the effect of these metals on pigmentation and on some enzymatic activities of the metal tolerant strains isolated, as well as antimicrobial resistance in some metal tolerant Enterobacteriaceae strains. Tolerance to Cr was observed mainly in Gram positive bacteria while in the case of Ag and Hg the tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 20 publications
0
40
0
1
Order By: Relevance
“…Under metal-stressed conditions, bacteria evolve various strategies and develop tolerance to survive [26]. Although heavy-metal cations are important as trace elements in biochemical reactions, at higher concentrations they lead to toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Under metal-stressed conditions, bacteria evolve various strategies and develop tolerance to survive [26]. Although heavy-metal cations are important as trace elements in biochemical reactions, at higher concentrations they lead to toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance genes may occur in bacterial chromosome or in plasmids and can be transmitted to other microbes via horizontal gene transfer similarly with antibiotic resistance genes [60]. For example, resistance genes for silver that have already been found in hospital environment [61,62] are located in mobile genetic elements easily transferable to other bacteria e.g., in (hospital) sewage systems [63]. Expression of biocide resistance genes has been associated with concurrent AMR [60,64].…”
Section: Resultsmentioning
confidence: 99%
“…solubilization and reduction) of heavy metals (Gadd 2000 ;Gadd and Griffi ths 1977 ). Various studies have demonstrated that certain soil microbes are capable of reducing and solubilizing metals such as Cr, Fe, Hg, Ag, Mn, Te and U, making them more or less available for plant absorption and minimizing their phytotoxicity (Giller et al 1998 ;Lima de Silva et al 2012 ;Watts and Lloyd 2012 ;Lasat 2002 ;Kashefi and Lovley 2000 ). Numerous studies have also reported that microbes were helpful in decreasing plant toxicity of Cd, Zn and Cr (Bennisse et al 2004 ;Juwarkar et al 2007 ;Khan 2005 ).…”
Section: Signifi Cance Of Soil Microbes and Inherent Heavy Metal Resimentioning
confidence: 99%